Molecular cloning and characterization of DNA fragments from Xanthomonas campestris pv. translucens and comparison with known sequences of Xanthomonas - Pretorius, Elize (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1993.